PENYULUHAN PENYEBAB DAN SOLUSI RETAK PADA DINDING RUMAH DI KELURAHAN BENDUNG, KOTA SERANG - Indrawati Sumeru; Suradjin Sutjipto; Darmawan Pontan; Khotijah Lahji (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
Cracks in the walls of the house are common. The cracks that occur are often only fine cracks that are not too disturbing, but sometimes you can see cracks in the walls that are relatively wide and deep. Fine cracks in walls are usually non-structural cracks, but cracks that are relatively wide and deep and have a certain direction are usually structural cracks. Structural cracks are the things that cannot be neglected because they may be dangerous for the occupants of the house. The condition of the people's houses in Kelurahan  Bendung, even the condition of the Kelurahan Bendung office itself, looks improper with the many cracks that have occurred. Cracks in walls are also commonly seen in the corners of door and window frames. In several locations, the cracks in the walls are quite wide and have a diagonal direction. This community service program is intended so that the PKM Team can provide sufficient technical knowledge to the residents of the Kelurahan Bendung regarding the types of cracks in the walls of their houses, what are the possible causes, and how to prevent and overcome them. The most important thing is that it is hoped that the community will have sufficient knowledge to be able to prevent structural cracks from occurring and to be able to recognize structural cracks that have the potential to endanger human life